Resistance to Phomopsis Seed Decay in Soybean. (22nd April 2013) - Li, Shuxian; Chen, Pengyin
Abstract : Phomopsis seed decay (PSD) of soybean is caused primarily by the fungal pathogen Phomopsis longicolla Hobbs along with other Phomopsis and Diaporthe spp. This disease causes poor seed quality and suppresses yield in most soybean-growing countries. Infected soybean seeds can be symptomless, but are typically shriveled, elongated, cracked, and have a chalky white appearance. Development of PSD is sensitive to environmental conditions. Hot and humid environments favor pathogen growth and disease development. Several control strategies have been used to manage PSD and reduce its impact; however, the use of resistant cultivars is the most effective method for controlling PSD. Efforts have been made to identify sources of PSD resistance in the past decades. At least 28 soybean lines were reported to have certain levels of PSD resistance in certain locations. Inheritance of resistance to PSD has been studied in several soybean lines. In this paper, general information about the disease, the causal agent, an overview of research on evaluation and identification of sources of resistance to PSD, and inheritance of resistance to PSD are presented and discussed.